Improving the Creativity of Early Children with the Method of Utilizing the Natural Environment in Pandemic Times - Ida Holida; Rita Aryani (Green Publisher Indonesia, 2021)
The low creativity of early childhood during the pandemic is because in learning from home children are only given worksheets and piles of assignments from school. In addition, the lack of stimulation given to children about utilizing the environment as a source of learning, makes children's creativity less optimal. This study aims to increase the creativity of early childhood with the method of utilizing the natural environment during the pandemic. This research is a qualitative research using classroom action research. The research subjects were conducted at PAUD Nurul Ilmi Cibinong Gunungsindur-Bogor. With this research, it is able to increase the creativity of early childhood through the use of learning resources from nature such as soil, stones, leaves, twigs, wood, water, clay and so on which can be utilized as much as possible.